ARISAN BACA TULIS: PEMBERANTASAN BUTA AKSARA MELALUI METODE ARISAN YANG UNIK DAN MENYENANGKAN - Kurniawati, Hamida; Sudewo, Arizky Rachmad; Fachrizal, Mochamad Sony; Firdausi, Khalida Putri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Surabaya as the capital of East Java was havenât Â free from illiteracy yet, the condition was mostly of them were women aged 30 years and over who havenât completed the compulsory education for nine years. In addition, women are also considered capable of transmitting knowledge and their knowledge to the family, especially the children as closest network. With the Â fun activity, we expect the new atmosphere of togetherness and gathering with the same degree of age are able to create its own preoccupations and improving the confidence to learn to read and write. This program, is modified such that mothers are often going ahead and daring to write or read the sentences given by instructor, will get a roll of paper that bearing their names. Thus, the more quantity Mothers forward and dare to write and read, the more the roll of their names, and a chance to win the raffle of âArisanâ at the end of training will be even greater. With different and unique method, able to attract mothers to be more diligent in reading and writing, so that illiteracy slowly be decrease, the mothers began to realize how important education started early, and spirit and motivation for learning has begun to form, evidenced by an increase in the ability of mothers to read and write, 77% of mothers who previously could not read, or only able to spell, and be able to read haltingly, and 68% of mothers who can not write, or can only write a few letters, as well as stuttering to write, has increased its ability to 86% have been able to read fluently, and 77% have been able to write correctly.Key Words: Illiteracy, Arisan, Literacy Education, Mothers of Keputih Tinja